2016
DOI: 10.7567/jjap.55.05ff03
|View full text |Cite
|
Sign up to set email alerts
|

Selective-area growth of GaN microrods on strain-induced templates by hydride vapor phase epitaxy

Abstract: In this paper, we discuss the influence of parameters such as type of carrier gas and NH3/HCl flow ratio on the growth of vertical GaN microstructures by selective-area growth (SAG) hydride vapor phase epitaxy (HVPE). On various strain-induced templates such as GaN/sapphire, GaN/Si, and AlN/Si, regular arrays of Ga-polar GaN microrods were properly achieved by adjusting the growth parameters. The photoluminescence and micro-Raman measurements reveal not only the crystal quality of the GaN microrods but also st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
(29 reference statements)
2
6
0
Order By: Relevance
“…surfaces in a large chemical potential range (except for (112 ̅ 2) surfaces under extremely Ga-rich condition). Also, (101 ̅ 2) surface, which was also revealed in experiments [55,56], is the most stable one in the region near Ga-rich. While it can also be observed under N-rich condition in experiments.…”
Section: / 12supporting
confidence: 66%
“…surfaces in a large chemical potential range (except for (112 ̅ 2) surfaces under extremely Ga-rich condition). Also, (101 ̅ 2) surface, which was also revealed in experiments [55,56], is the most stable one in the region near Ga-rich. While it can also be observed under N-rich condition in experiments.…”
Section: / 12supporting
confidence: 66%
“…The NBE of the GaN NRs peaked at 3.49 eV, slightly higher than the typical peak of neutral donor-bound excitons (D 0 X), which appears at 3.47 eV. This slight increase might arise from compressive strain of the GaN NRs as well as Si impurities dissociated from the mask535455. The compressive strain of GaN NRs was confirmed by Raman spectroscopy (see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 78%
“…In the HVPE process, the growth temperature, which is higher than 600 °C, is supposed to be high enough to overcome this limitation. Furthermore, previous studies demonstrated that the radial growth rate of GaN rods grown by HVPE decreases at a high partial pressure of HCl and/or H2 [26], [27] . These findings are in accordance with the theoretical results dealing with the effect of H2 on the growth rate of non-polar GaN (1-100) surfaces [36] .…”
Section: Resultsmentioning
confidence: 95%
“…Crystal shape engineering of nitride structures by SAG-HVPE can be carried out by varying the vapor-phase composition and the growth temperature. These experimental parameters govern the kinetics involved in the growth process. Understanding how each parameter impacts the crystal growth of InN is important to monitor the formation of the nanorods. To the best of our knowledge, no study has ever been carried out to understand and ultimately control the SAG of InN nanorods.…”
Section: Introductionmentioning
confidence: 99%